The Effect of Differentiated Learning on the Conceptual Understanding and Mathematical Calculation Skills of Fifth Grade Students of SD Negeri 6 Sangia Wambulu - Upik Erdawati S Sianu; Raden Sumiadi; Abdul Aziz (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The low conceptual understanding and mathematical calculation skills of elementary school students remain a challenge in improving the quality of learning. Uniform and procedural-oriented learning has not fully accommodated differences in student learning readiness, resulting in students having difficulty understanding the meaning of concepts and lacking the skills to perform arithmetic operations accurately and confidently. Although differentiated learning has been widely studied theoretically, empirical evidence regarding the effectiveness of differentiated learning-based learning readiness processes on these two aspects is still limited. This study aims to analyze the effect of differentiated learning on conceptual understanding and mathematical calculation skills of fifth-grade students. The study used a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The research subjects were 27 students, consisting of 16 students from the experimental class and 11 students from the control class. The research instruments included a conceptual understanding test and a mathematical skills test. Data were analyzed using normality tests, homogeneity tests, paired sample t-tests, Wilcoxon tests, and Mann-Whitney tests at a significance level of 0.05. The results showed that differentiated learning significantly influenced students' conceptual understanding and mathematical skills (p < 0.05). In addition, there was a positive and significant relationship between conceptual understanding and mathematical skills. These findings indicate that process differentiation based on learning readiness is effective in strengthening conceptual construction while increasing elementary school students' mathematical fluency and accuracy.